2010
DOI: 10.1111/j.1365-2265.2010.03893.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of [111In]pentetreotide‐SPECT and [18F]FDOPA‐PET in the localization of extra‐adrenal paragangliomas: the case for a patient‐tailored use of nuclear imaging modalities

Abstract: The sensitivity of SRS for localizing parasympathetic PGLs is lower than originally reported, and [¹⁸F]FDOPA-PET is better than SRS for localizing small lesions. SRS should be replaced by [¹⁸F]FDOPA-PET as the first-line imaging procedure in H&N PGL, especially in patients at risk of multifocal disease (predisposing mutations and or previous history of surgery).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…These results are in line with those obtained by Charrier et al, who found a sensitivity of 97% for 18 F-FDOPA PET/ CT versus 67% for SST scintigraphy (34). This lower sensitivity of SST scintigraphy probably is related to the limited resolution of SPECT.…”
Section: Hnpssupporting
confidence: 82%
See 3 more Smart Citations
“…These results are in line with those obtained by Charrier et al, who found a sensitivity of 97% for 18 F-FDOPA PET/ CT versus 67% for SST scintigraphy (34). This lower sensitivity of SST scintigraphy probably is related to the limited resolution of SPECT.…”
Section: Hnpssupporting
confidence: 82%
“…In a prospective study by Fottner et al, all sympathetic paragangliomas associated with SDH mutations were positive with 123 I-MIBG, whereas 2 extraadrenal paragangliomas were not detected with 18 F-FDOPA PET despite the centimeter size of the lesions (54). This possibility of missing certain retroperitoneal tumors has also been noted in 3 other studies (34,53,56). 18 F-FDA PET is highly sensitive but may also miss some tumors (24,60).…”
Section: Extraadrenal Retroperitoneal Paragangliomasmentioning
confidence: 84%
See 2 more Smart Citations
“…In-Octreotide is a somatostatin analog with modest sst2 binding that has been reported to have a good sensitivity for head and neck paragangliomas, up to 90 % [7], but a lower sensitivity for detecting paragangliomas overall (74 % reported by Charrier in 2011) with a sensitivity as low as 20 % for abdominal paragangliomas [8]. Ga-DOTATATE PET/CT sensitivity of 80 % in the detection of pheochromocytomas and paragangliomas, superior to 123 I-MIBG [11], and Naswa Ga-DOTANOC in 26 head and neck paraganglioma patients [13].…”
mentioning
confidence: 99%